The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/1932296814543946
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a New Patch Pump Based on a Microelectromechanical System (MEMS) Compared to Other Commercially Available Insulin Pumps

Abstract: Background: The JewelPUMP™ (JP) is a new patch pump based on a microelectromechanical system that operates without any plunger. The study aimed to evaluate the infusion accuracy of the JP in vitro and in vivo. Methods:For the in vitro studies, commercially available pumps meeting the ISO standard were compared to the JP: the MiniMed® Paradigm® 712 (MP), Accu-Chek® Combo (AC), OmniPod® (OP), Animas® Vibe™ (AN). Pump accuracy was measured over 24 hours using a continuous microweighing method, at 0.1 and 1 IU/h b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 21 publications
3
48
1
Order By: Relevance
“…Switching from multiple daily infusion (MDI) to continuous subcutaneous insulin infusion (CSII) induces well-known advantages, including the reduction of swings in blood glucose levels and the limitation of severe hypoglycemia [5][6][7]. In addition, this MEMS-based micropump provides outstanding delivery accuracy and failure detection capabilities, as reported in recent in vitro and in vivo studies comparing the pumping capability of several pump systems [8]. In this paper, the emphasis is placed on the description of the integrated pressure sensors and their typical experimental responses in various conditions.…”
Section: Introductionmentioning
confidence: 96%
“…Switching from multiple daily infusion (MDI) to continuous subcutaneous insulin infusion (CSII) induces well-known advantages, including the reduction of swings in blood glucose levels and the limitation of severe hypoglycemia [5][6][7]. In addition, this MEMS-based micropump provides outstanding delivery accuracy and failure detection capabilities, as reported in recent in vitro and in vivo studies comparing the pumping capability of several pump systems [8]. In this paper, the emphasis is placed on the description of the integrated pressure sensors and their typical experimental responses in various conditions.…”
Section: Introductionmentioning
confidence: 96%
“…Median (interquartile range (IQR)) age at the start of pump use was 40 (30, 49) years and median diabetes duration was 20 (11,29) years. Initial pump models were: 50% Medtronic, 24% Omnipod (patch pump), 14% Roche and 12% Animas.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, Jahn et al showed that the accuracy of the patch pump was lower than that of traditional pumps. In another study by Borot et al, the Omnipod pump was again the least accurate of the pumps tested [11]. However, there has been criticism of the methods used in the studies [16].…”
Section: Previous Studies Comparing Pump Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…We also are analyzing the certification requirements established by ANVISA (Brazilian agency of health surveillance). The accuracy of insulin pumps is of great concern, especially in cases with low infusion rates, where they can limit glycemic variability and unexplained hypo-or hyperglycemic events unawares [8]. So, the next step of the prototype development will start with in vitro studies, using a continuous microweighing method to measure water delivery, and evaluate the accuracy of our prototype.…”
Section: Discussionmentioning
confidence: 99%